West African Monetary Integration and Interstates Risk-Sharing - (:unkn) unknown (My University, 2011)
There are continuing efforts at the monetary integration and unionization in West Africa. Several academics argue that a monetary union among West African states would be costly because of the magnitude of asymmetric shocks. A common monetary policy is inappropriate and ineffective to respond to divergent shocks. Therefore, the stability of such a union is critically dependent on risk-sharing mechanisms for achieving income insurance and consumption smoothing. A monetary union is still optimal if output stabilization mechanisms such as risk-sharing institutions, are in place to cope with asymmetric shocks. This article estimates risk-sharing channels among West African states from 1970 to 2004. It uses the definition of national accounts to measure the fraction of asymmetric output shocks smoothed via net factors income, net transfers and net saving. We find that compared to the OECD (Organization for Economic Cooperation and Development) estimates, the degree of risk-sharing among West African countries is quite low. We also obtain that net saving is the significant and stable risk-sharing channel. A further analysis shows that only the contribution of public saving is significant.
Keywords: African Research